Tracer Tests For Heterogeneity Characterization And Saturation Determination On Core Flooding - Sugihardjo Sugihardjo; Usman Usman; Utomo Pratama I (Testing Center for Oil and Gas LEMIGAS, 2010)
Low sweep efficiency is the common problem in displacement process due to heterogeneity, high permeability streaks, fractures, and thief zones existing in the formation. Similarly, the success or failure of EOR implementations are always affected by those problems which causes displacing fluids fingering and early breakthrough. Factors of this type, unless properly identified and understood before the start of EOR process, will likely cause a project failure. Core flooding as the model of small scale of fluids movements in reservoir undergoes similar circumstances. Approximately one foot long of four 3.5 inches stacked native and synthetic cores are normally used in core flooding experiment. Tracer test was performed to characterize the core in addition of CT scan analysis. On this experiment, lithium solution was selected as tracer solution to be then injected into core at constant rate, 4 ft/day. Afterwards, the effluents were collected by Gilson sample collector in each tube for further determinination its concentration using Atomic Absorption Spectrometry (AAS). Response curves of lithium tracer were able to determine core heterogeneities and this should be done to avoid misleading interpretation of core flooding results. Besides, lithium concentration reported in some extent and subsequently analyzed by employing method of temporal moments. This method provides numerical calculation to estimate effective core pore volume (PV) and fluid saturation. Weighing method was also used to compare the PV with aforementioned method and the results were comparable.